Dimensionamento de estrutura para galpão industrial em perfis formados à frio de acordo com a ABNT NBR 14762:2010 - Dobkowski, Lucas Cardoso (2018)
This work presents the application of the norm NBR 14762 (2010) in the design of a structure of industrial shed constituted by profiles of steel formed to cold, as well as the calculation of the permanent and variable actions that this structure can suffer when elapsing of her life, as for instance the action of the calculated wind according to NBR 6123 (1988).The great influence of the industrial sector in the city of Pato Branco and its imminent growth brings with it the need of works related to the dimensioning of properties projected for the industry, what justifies the existence of this work. The sizing was carried out from calculations using the established equations and also with software support for structural simulation. Calculations made and computational simulations.